2016
DOI: 10.1038/srep19902
|View full text |Cite
|
Sign up to set email alerts
|

Stable solid and aqueous H2CO3 from CO2 and H2O at high pressure and high temperature

Abstract: Carbonic acid (H2CO3) forms in small amounts when CO2 dissolves in H2O, yet decomposes rapidly under ambient conditions of temperature and pressure. Despite its fleeting existence, H2CO3 plays an important role in the global carbon cycle and in biological carbonate-containing systems. The short lifetime in water and presumed low concentration under all terrestrial conditions has stifled study of this fundamental species. Here, we have examined CO2/H2O mixtures under conditions of high pressure and high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 35 publications
7
25
0
1
Order By: Relevance
“…Recently, a new CO 2 -H 2 O compound was observed above 2.4 GPa and asserted to be H 2 CO 3 based on IR and Raman lines similar to those of the low pressure H 2 CO 3 solid (Wang et al 2016). Following this initial report, we (Abramson et al 2017) demonstrated that this new phase can exist in equilibrium with an aqueous fluid (starting from a quadruple point with ices H 2 O(VII) and CO 2 (I), at 4.4 GPa and 165 °C), which allowed the growth of single crystals for purposes of X-ray diffraction.…”
Section: Prior Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new CO 2 -H 2 O compound was observed above 2.4 GPa and asserted to be H 2 CO 3 based on IR and Raman lines similar to those of the low pressure H 2 CO 3 solid (Wang et al 2016). Following this initial report, we (Abramson et al 2017) demonstrated that this new phase can exist in equilibrium with an aqueous fluid (starting from a quadruple point with ices H 2 O(VII) and CO 2 (I), at 4.4 GPa and 165 °C), which allowed the growth of single crystals for purposes of X-ray diffraction.…”
Section: Prior Studiesmentioning
confidence: 99%
“…However, owing to unfavorable kinetics and equilibrium constants at ambient conditions (Loerting et al 2000), molecular carbonic acid has 3 long eluded detailed experimental observation and, as described below, a crystalline structure had not previously been determined. Recently, Wang et al (2016) claimed to have observed the formation of solid carbonic acid at high pressures, and Abramson et al (2017) demonstrated that the observed phase can exist in thermodynamic equilibrium with the aqueous fluid for pressures beyond a quadruple point at 4.4 GPa. Preliminary X-ray results indicated that the new phase was triclinic, but their quality did not allow a refinement of the crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…On Earth, H 2 CO 3 is found in a solution with water (H 2 O) and carbon dioxide (CO 2 ). It plays an important role in the global carbon cycle and in biological carbonate-containing systems (Wang et al 2016). For instance, about 30 − 40% of human-induced emissions of atmospheric Send offprint requests to: S. Ioppolo; e-mail: s.ioppolo@qmul.ac.uk CO 2 dissolve into the oceans to form carbonic acid (Caldeira & Wickett 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This information can be used to model and understand the interiors of giant exoplanets 22 . Wang et al 23 have shown that contrary to earlier understanding, carbonic acid could be a stable species in the aqueous fluids found in the subduction zone of the earth (P > 2.4 GPa). Even simple oxides of iron like hematite and magnetite decompose at 60-70 GPa and 2500 K to release large amounts of oxygen and form novel oxides of iron.…”
Section: Introductionmentioning
confidence: 39%